Dalbavancin for treating prosthetic joint infections caused by Gram-positive bacteria: A proposal for a low dose strategy. A retrospective cohort study - Martín, Luis Buzón (Rev Esp Quimioter, 2019)
BACKGROUND: Gram-positive bacteria are the leading cause of prosthetic joint infection (PJI). Dalbavancin is a lipoglycopeptide with remarkable pharmacokinetic properties and high bactericidal activity against most Gram-positive bacteria. Although clear evidence regarding its effectiveness in bone and joint infections lacks, recent studies suggest a promising role of dalbavancin in PJI. METHODS: From June 1st 2016 to May 1st 2018, all patients diagnosed of PJI and treated with DAL alone or in combination with other drugs were retrospectively evaluated. Dalbavancin susceptibility of every isolate was studied following CLSI criteria. The primary objective was to assess the clinical efficacy and tolerability of the drug in patients with PJI. A cost-analysis was performed following the DALBUSE study methodology. RESULTS: Sixteen patients were treated with dalbavancin, eight with total hip arthroplasty infection (THAi) and eight with total knee arthroplasty infection (TKAi). Staphylococcus spp. and Enterococcus spp. were the microorganisms involved. No major side effects were detected. Infection resolved in 12 patients. In 2 patients the treatment failed, and another patient died due to unrelated causes. One patient is currently being treated for hematogenous-spread knee infection secondary to prosthetic aortic arch endocarditis. After discontinuation of dalbavancin, and excluding patients who died or with clinical failure, the median follow up of the cohort was 503 days (interquartile range IQR, 434.5 to 567 days). We calculate that US$ 264,769 were saved. CONCLUSION: This study suggests that dalbavancin treatment for PJI caused by Gram-positive bacteria is a safe and effective option that reduces hospital stay and costs. Future reports are needed to confirm these findings.